2022
DOI: 10.1007/s00520-022-06855-4
|View full text |Cite|
|
Sign up to set email alerts
|

Acceptance of disability, coping style, perceived social support and quality of life among patients with chronic lymphedema: a cross-sectional study

Abstract: Objective: To examine acceptance of disability, coping style, perceived social support, and quality of life and to explore the relationships between acceptance of disability, coping style, perceived social support and quality of life among Chinese patients with chronic lymphedema. Methods: Chronic lymphedema patients were recruited from ve tertiary hospitals between May and July 2020 in China. Recruited patients were assessed for quality of life (QOL), acceptance of disability (AOD), coping styles, perceived s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Similar to our study, previous studies demonstrated a negative association between resignation and QoL among patients with chronic lymphedema and breast cancer. 23,31 As expected, our study revealed that resignation partially mediated the relationship between self-efficacy and QoL. In other words, higher self-efficacy can reduce patients' use of resignation coping when facing CHBrelated stress and accordingly improve their QoL.…”
Section: Discussionsupporting
confidence: 77%
“…Similar to our study, previous studies demonstrated a negative association between resignation and QoL among patients with chronic lymphedema and breast cancer. 23,31 As expected, our study revealed that resignation partially mediated the relationship between self-efficacy and QoL. In other words, higher self-efficacy can reduce patients' use of resignation coping when facing CHBrelated stress and accordingly improve their QoL.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, in this study, the total DASS-21 scores of persons with disability who received social support in family members were found to be lower. In studies conducted with people with and without disabilities, it is reported that high social support reduces perceived stress and depression levels ( Deegan & Dunne, 2022 ; Fisher et al, 2022 ; Huang & Wu, 2022 ; Proescher et al, 2022 ). In the findings of the study, the reason for the lower levels of depression, anxiety, and stress in persons with disability may be the social support that PWD receive from family members is generally continuous and long-term in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Social support is an essential resource for helping people, especially women, overcome hardships, such as natural disasters [ 67 , 68 ]. Therefore, it is not astonishing that functional outcomes were better in persons experiencing chronic pain who had good social support systems than in their counterparts with limited social interactions [ 69 , 70 , 71 , 72 ]. Social isolation can be a significant predictor of pain-induced disability in persons with lower back pain, presumably by negatively influencing self-efficacy and the way patients with chronic pain cope with the disease [ 73 ].…”
Section: Discussionmentioning
confidence: 99%